Hubungan Antara Status Gizi dan Aktivitas Fisik dengan Kejdian Dimensia - Rani Oktarina (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2020)
Based on the results of the 2014 National Socio-Economic Survey, the number of elderly people in Indonesia reached 20.24 million or around 8.03% of the total population of Indonesia. The purpose was to determine the relationship between nutritional status and physical activity with the incidence of dementia in Prabumulih City Market Health Center in 2019. This study uses Analytical Survey using the Cross-Sectional approach. The population is elderly people aged 45-59 years, amounting to 94 people. The sample amounted to 94 respondents. In the univariate analysis of 94 respondents, it was found that respondents with good nutritional status were 56 respondents (59.6%) and respondents with malnutrition status were 38 respondents (40.4%). Good physical activity was 52 respondents (55.3%) and respondents who had bad physical activity were 42 respondents (44.7%). Bivariate analysis showed Nutritional Status had a significant relationship with the incidence of dementia (p-value 0.003) and Physical Activity had a significant relationship with the incidence of dementia (p-value 0.001). This study concludes that there is a relationship between nutritional status and physical activity with the incidence of dementia in Prabumulih City Market Health Center in 2019.